2018
DOI: 10.1021/acs.biochem.8b00582
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MEMO1 Binding Specificity for ErbB2 Using Fluorescence Polarization and Molecular Dynamics Simulations

Abstract: ErbB2 signaling pathways are linked to breast cancer formation, growth, and aggression; therefore, understanding the behavior of proteins associated with these pathways as well as regulatory factors that influence ErbB2 function is essential. MEMO1 is a redox active protein that is shown to associate with phosphorylated ErbB2 and mediate cell motility. We have developed a fluorescence polarization assay to probe the interaction between MEMO1 and an ErbB2-derived peptide containing a phosphorylated tyrosine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Through an unbiased screen, MEMO1 was shown to interact with phospho-Tyrosine (pY) 1227 on the C-terminus of ERBB2 after ligand (Heregulin, HRG) stimulation-a residue shown to be important for tumor cell migration [1]. Since its initial isolation, MEMO1 s interaction with ERBB2 is by far the most well characterized, relative to other signaling pathways [1,3,[7][8][9][10][11][12][13]. Given MEMO1 does not display any obvious SH2 or phospho-tyrosine binding domains, its interaction with pY1227 was thought to be mediated, in part, through the Src homology and collagen 1 (SHC) adaptor protein [1] ( Figure 1A).…”
Section: Part Imentioning
confidence: 99%
See 2 more Smart Citations
“…Through an unbiased screen, MEMO1 was shown to interact with phospho-Tyrosine (pY) 1227 on the C-terminus of ERBB2 after ligand (Heregulin, HRG) stimulation-a residue shown to be important for tumor cell migration [1]. Since its initial isolation, MEMO1 s interaction with ERBB2 is by far the most well characterized, relative to other signaling pathways [1,3,[7][8][9][10][11][12][13]. Given MEMO1 does not display any obvious SH2 or phospho-tyrosine binding domains, its interaction with pY1227 was thought to be mediated, in part, through the Src homology and collagen 1 (SHC) adaptor protein [1] ( Figure 1A).…”
Section: Part Imentioning
confidence: 99%
“…However, follow-up studies, including elucidation of the MEMO1 crystal structure, have shown that MEMO1 can bind directly to pY1227 through a binding pocket contained within the protein, originally termed a 'vestigial active site' [3]. While quite extensive analyses, using an array of approaches, have been used to elucidate the key residues that mediate this interaction [3,8,11] (e.g., W16, H49, Y54, H81, D189, H192, R196, R198, C244) there have been some discrepancies. For example, while residues H81, H192 and C244 were previously shown to be essential for MEMO1 binding to an ERBB2 peptide [3], follow-up studies suggested these residues may be dispensable (or less important) for MEMO1 binding.…”
Section: Part Imentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ErbB2 expression is specific to RGs and its loss of function in the mouse unbalances the astrocyte/RG population ratio by reducing the number of elongated RGs in the developing cortex (Schmid et al, 2003). ErbB2 interacts specifically with a redox active protein, Memo1 (Newkirk et al, 2018). Although Memo1 has been known for some time to be important for cell migration (Marone et al, 2004), its role in the branching and the maintenance of the RG scaffold was identified relatively recently (Nakagawa et al, 2019).…”
Section: Secreted Factors From Close Range Cellsmentioning
confidence: 99%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%